2008
DOI: 10.1089/rej.2008.0716
|View full text |Cite
|
Sign up to set email alerts
|

Carnisone Increases Efficiency of DOPA Therapy of Parkinson's Disease: A Pilot Study

Abstract: The addition of the neuropeptide carnosine (beta-alanyl-L-histidine) as a food additive to the basic protocol of Parkinson's disease treatment results in significant improvement of neurological symptoms, along with increase in red blood cell Cu/Zn-SOD and decrease in blood plasma protein carbonyls and lipid hydroperoxides, with no noticeable change in platelets MAO B activity. The combination of carnosine with basic therapy may be a useful way to increase efficiency of PD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 18 publications
2
62
1
3
Order By: Relevance
“…The unexpected role of anticonvulsants as anti-ageing agent, at least in nematodes, and the association of carnosine/homocarnosine with anticonvulsant activity in rodents and humans are further testament to the enigmatic pluripotency of this almost non-toxic peptide. Possible beneficial effects of the dipeptide on agerelated pathologies such as diabetes (Hipkiss, 2005(Hipkiss, & 2006c, Alzheimer's disease (Hipkiss, 2007c), Parkinsons's disease (Boldyrev et al, 2008) and stroke (Dobrota et al, 2005) have therefore been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…The unexpected role of anticonvulsants as anti-ageing agent, at least in nematodes, and the association of carnosine/homocarnosine with anticonvulsant activity in rodents and humans are further testament to the enigmatic pluripotency of this almost non-toxic peptide. Possible beneficial effects of the dipeptide on agerelated pathologies such as diabetes (Hipkiss, 2005(Hipkiss, & 2006c, Alzheimer's disease (Hipkiss, 2007c), Parkinsons's disease (Boldyrev et al, 2008) and stroke (Dobrota et al, 2005) have therefore been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, high levels of carnosine and related histidyl peptides (anserine, homocarnosine) are also present in aerobic tissues such as the heart and the brain, suggesting that carnosine might have other functions as well. Previous studies have shown that carnosine protects against ischemic injury (24 -26), hyperglycemia (27), neurodegenerative diseases (28), and aging (29,30). Collectively, these findings indicate that in addition to buffering intracellular pH, carnosine might have an antioxidant role in removing aldehydes (31).…”
mentioning
confidence: 99%
“…As previously discussed, carnosine counteracts MG and other cytotoxic aldehydes [50], which in part could substantiate its neuroprotective effect in PD patients. A pilot study performed by Boldyrev and colleagues [99] assessed the efficacy of carnosine (1.5 g, daily, by 30 days) as a complement to DOPA drug therapy in PD patients. It was concluded that the combination of carnosine with basic therapy for certain PD patients may be a reasonable way to improve the protocol of PD treatment and to decrease the possible toxic effects of the overloading of DOPA-containing drugs [99].…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
“…A pilot study performed by Boldyrev and colleagues [99] assessed the efficacy of carnosine (1.5 g, daily, by 30 days) as a complement to DOPA drug therapy in PD patients. It was concluded that the combination of carnosine with basic therapy for certain PD patients may be a reasonable way to improve the protocol of PD treatment and to decrease the possible toxic effects of the overloading of DOPA-containing drugs [99]. Due to the small number of volunteers and the short duration of this study, a larger and long-term trial is needed to confirm the benefit of carnosine combined to DOPA drug therapy.…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%